Reflections on Trash-humanism as Performed by Jaime del Val - Tuncel, Yunus (Journal of Posthumanism, 2023)
In the online event, Metahuman Futures Forum, which took place in August 2022 and was coorganized by Reverso/Metabody and the Posthuman Lab, I had reflected on Jaime del Val’s ‘Trashhuman Enhancement and Planetary Health’ and made the following observations, which can be grouped in five parts: a) the place of the body and embodiment; b) relational ethics; c) alternatives and the healing process; d) transvaluation and what the future holds for humanity; e) protestation, resistance and cultural transformation without utopianism